2015
DOI: 10.1097/mca.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Expression of coinhibitory PD-L1 on CD4+CD25+FOXP3+ regulatory T cells is elevated in patients with acute coronary syndrome

Abstract: Expression of the coinhibitory molecule PD-L1 on peripheral blood Tregs is correlated negatively with the severity of CHD and could serve as a novel indicator of ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In our study, the serum levels of IL-6, TNF- α , and IFN- γ were significantly higher in ACS patients than in controls, which was in accordance with previous studies [8, 14, 1921]. As an anti-inflammatory cytokine, the serum IL-4 levels in CAD patients were controversial [2224]. We found lower levels of IL-4 in AMI patients, as compared with controls and SAP patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the serum levels of IL-6, TNF- α , and IFN- γ were significantly higher in ACS patients than in controls, which was in accordance with previous studies [8, 14, 1921]. As an anti-inflammatory cytokine, the serum IL-4 levels in CAD patients were controversial [2224]. We found lower levels of IL-4 in AMI patients, as compared with controls and SAP patients.…”
Section: Discussionsupporting
confidence: 91%
“…In cardiovascular disease patients, altered levels of circulating PD-1 and PD-L1 expressing cells have been reported ( 16 , 17 ). For example, PD-1 expression on circulating T cells was decreased compared to healthy control individuals and concomitantly, decreased PD-L1 expression on APCs was reported, which corresponded to increased T cell responses ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, T cell population and FOXP3 levels has been shown to be decreased in patients with ACS compared with stable angina and normal coronary arteries patients . Besides, a recent study has shown higher expression of the coinhibitory molecule PD‐L1 on peripheral blood Tregs in patients with ACS compared with chronic coronary artery disease and controls . The observed lower expression of FOXP3 as well as Th17/Treg functional imbalance in patients with ACS have implied a potential role for Th17/Treg disparity in plaque destabilization and the occurrence of ACS .…”
Section: Discussionmentioning
confidence: 91%
“…14 Besides, a recent study has shown higher expression of the coinhibitory molecule PD-L1 on peripheral blood Tregs in patients with ACS compared with chronic coronary artery disease and controls. 15 The observed lower expression of FOXP3 as well as Th17/Treg functional imbalance in patients with ACS have implied a potential role for Th17/Treg disparity in plaque destabilization and the occurrence of ACS. 4 In the present study we evaluated the expression of FOXP3 in ACS as well as the MI and UA subgroups in both sexes.…”
Section: Discussionmentioning
confidence: 99%